Investigation of the link between fluid shift and airway collapsibility as a mechanism for obstructive sleep apnea in congestive heart failure - Carlisle,T; Ward,NR; Atalla,A; Cowie,MR; Simonds,AK; Morrell,MJ (Physiological Reports, 2017)
The increased prevalence of obstructive sleep apnea (OSA) in congestive heart failure (CHF) may be associated with rostral fluid shift. We investigated the effect of overnight rostral fluid shift on pharyngeal collapsibility (Pcrit), pharyngeal caliber (APmean), and apneahypopnea index (AHI) in CHF patients. Twentythree optimally treated systolic CHF patients were studied. Neck circumference was measured immediately prior to sleep in the evening and immediately after waking in the morning as a marker of rostral fluid shift. Pcrit was measured during sleep, early and late in the night. APmean was measured using acoustic reflection at the same times as neck circumference measurements. 15/23 CHF patients experienced an overnight increase in neck circumference; overall neck circumference significantly increased overnight (mean±SD, evening: 41.7 ± 3.2 cm; morning: 42.3 ± 3.1 cm; P = 0.03). Pcrit increased significantly overnight (earlynight: −3.8 ± 3.3 cmH2O; latenight: −2.6 ± 3.0 cmH2O; P = 0.03) and APmean decreased (evening: 4.2 ± 1.3 cm2; morning: 3.7 ± 1.3 cm2; P = 0.006). The total AHI correlated with neck circumference (r = 0.4; P = 0.04) and Pcrit (r = 0.5; P = 0.01). APmean correlated with neck circumference (r = −0.47; P = 0.02). There was no significant change in AHI between the first and second half of the night (firsthalf: 12.9 ± 12.4/h; secondhalf: 13.7 ± 13.3/h; P = 0.6). Overnight rostral fluid shift was associated with increased pharyngeal collapsibility and decreased pharyngeal caliber during sleep in CHF patients. Rostral fluid shift may be an important mechanism of OSA in this patient group.